ANALISIS DISPARITAS DAN PENGARUH PDRB PERKAPITA, BELANJA MODAL, JUMLAH PENDUDUK MISKIN DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP IPM KABUPATEN DAN KOTA DI PROVINSI JAMBI - Rizky Mulyawan; Yulmardi; Hardiani (Jurnal Riset Multidisiplin Edukasi, 2026)
This research is motivated by the disparity in the Human Development Index (HDI) between districts/cities in Jambi Province, which reflects inequality in the quality of human development. This difference in development levels is a crucial issue because it can impact community welfare and equitable development across regions. Therefore, this study aims to analyze the disparity in the HDI among districts/cities and to calculate the influence of per capita GDP, capital expenditure, the number of poor people, and the open unemployment rate on the HDI of districts and cities in Jambi Province from 2017 to 2024. The analytical methods used in this study include descriptive and quantitative analysis, using the Williamson Index to measure the level of HDI inequality, and panel data regression to analyze the influence of variables affecting the HDI. The results indicate that during the 2017–2024 period, there was moderate HDI inequality in Jambi Province. However, the HDI gap between districts/cities tended to increase in the 2021–2024 period.  Furthermore, the regression analysis results show that GRDP per capita, capital expenditure, the number of poor people, and the unemployment rate significantly influence the HDI in Jambi Province.